(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effect of financial literacy and pocket money on financial management in MBKM Management Study Program students in 2021, Panca Budi Development University, the type of research used in this study is associative research, the population in this study are MBKM Management Study Program students, Faculty of Social Sciences, Panca Budi Development University, class of 2021, totaling 176 people, the sampling technique used is the slovin method with a sample size of 64 people, the data analysis technique used in this study is multiple linear regression, the results of this study show that in this study the financial literacy variable has a positive and significant effect on financial management in MBKM Management Study Program students in the class of 2021, Panca Budi Development University seen from the calculated t value (3,700)> t table (1,999) and a significance level of 0.000 <0.05, In this study the pocket money variable has a positive and significant effect on financial management in MBKM Management Study Program students in the class of 2021, Panca Budi Development University Panca Budi, seen from the calculated t value (6.096)> t table (1.999) and a significance level of 0.005 <0.05, the independent variables consisting of Financial Literacy and Pocket Money simultaneously have a significant effect on financial management in MBKM students of the Management Study Program, Class of 2021, Panca Budi Development University.